2014
DOI: 10.1007/s11011-014-9534-3
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated homocysteine level in first-episode schizophrenia patients—the relevance of family history of schizophrenia and lifetime diagnosis of cannabis abuse

Abstract: Accumulating evidence indicates that elevated homocysteine (Hcy) level occurs in first-episode schizophrenia (FES) patients. We included 56 FES patients and 53 healthy controls (HC). Plasma level of Hcy was significantly higher in FES patients than HC (p = 0.044). In addition, plasma levels of high-density lipoproteins (HDL) and folate were significantly lower in FES than in HC (p < 0.001). Positive family history of schizophrenia was associated with lower plasma HDL (p = 0.041) and vitamin B12 (p = 0.017), as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 74 publications
4
36
2
3
Order By: Relevance
“…On the one hand, the severity of general psychopathology was related to higher homocysteine levels, as the previous study reported (45). However, we did not replicate previous findings of a positive correlation between homocysteine and severity of negative symptoms (45)(46)(47). On the other hand, LPO levels seemed to be lower in patients with greater severity of negative symptoms, measured by both the PANSS and BNSS scales.…”
Section: Discussioncontrasting
confidence: 99%
“…On the one hand, the severity of general psychopathology was related to higher homocysteine levels, as the previous study reported (45). However, we did not replicate previous findings of a positive correlation between homocysteine and severity of negative symptoms (45)(46)(47). On the other hand, LPO levels seemed to be lower in patients with greater severity of negative symptoms, measured by both the PANSS and BNSS scales.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, this study revealed that 31% of cannabis users, who later developed schizophrenia stopped using cannabis before the day of conscription, suggesting that cannabis may exert long-term deleterious effects with respect to the development of psychosis (Zammit et al, 2002). Our group has also shown that lifetime diagnosis of cannabis abuse might be associated with one-carbon metabolism disturbances and dyslipidemia (Misiak et al, 2014).…”
Section: Substance Use Disordersmentioning
confidence: 63%
“…Numerous factors underlie the burden of MetS including antipsychotic treatment, sedentary life style, poor dietary habits, low physical activity, the severity of negative symptoms and cognitive impairment. It should also be noted that first-episode schizophrenia patients display mild features of metabolic deregulation in terms of insulin resistance Ryan et al, 2003;Wu et al, 2013), dyslipidemia Misiak et al, 2014;Wu et al, 2013), increased serum levels of IL-6 or TNF-␣ and adiponectin (Song et al, 2013) as well as lower levels of polyunsaturated fatty acids (McEvoy et al, 2013). However, pharmacological treatment, especially second-generation antipsychotics (SGA) seem to be the major risk factor for MetS development (Hasnain et al, 2010).…”
Section: Medical Comorbiditymentioning
confidence: 99%
“…However, changes in DNA methylation correlated with the folate status. Two single nucleotide polymorphisms (C677T and A1298C) in the methylenetetrahydrofolate (MTHFR) gene are important genetic predictors of Hcy level [8].…”
Section: Homocysteine Metabolismmentioning
confidence: 99%